Toxicological and chemical studies of wastewater from hydraulic fracture and conventional shale gas wells. (11th June 2018) - Crosby, L.M.; Tatu, Calin A.; Varonka, Matthew; Charles, Kaylene M.; Orem, William H.
Abstract: New technology has enabled recovery of inaccessible natural gas shale deposits; however, the potential impacts to human health from the migration of brines into drinking water or surface spills are unknown. To provide information that can inform these potential impacts, chemical characterization and in vitro toxicologic testing were conducted using pre‐ and postinjection waters from conventional and unconventional oil and gas wells. Wastewater concentrations may be diluted or reduced by fate and transport processes when released into the environment by unknown amounts, and laboratory studies only imply potential effects. In acute cytotoxicity and wound healing assays, there was dose‐dependent toxicity in human and rat cells with growth promotion at low concentrations. Lethality was measured in time studies up to 10 d postinjection. Produced water samples from both well types were equally toxic to human cells and were corrosive at high concentrations. Measurement of protein and gene expression identified metabolic pathways responding to both well types as NADPH quinone oxidoreductase oxidative stress‐responsive enzyme and tight junction protein genes. A KCl sample of matched ionic strength showed a different toxicity profile from produced waters, indicating that salts alone were not the cause of toxicity. Organic chemicals and branched alkanes were present in hydraulic fracture wells, and mainly branched alkanes were present in conventional wells. One organic substance was still present after 240 d. The known properties of these chemicals include potential toxicity to multiple human organs, sensitization, irritation, developmental effects, and tumor promotion, depending on the concentrations and synergistic effects of chemicals during exposure. Environ Toxicol Chem 2018;37:2098–2111. © 2018 SETAC